PRODUCTION OF NITRILE GROUP-CONTAINING ORGANIC POLYMERIC ARTICLE - IWATA SETSUO (1998)
PROBLEM TO BE SOLVED: To enable the production of the subject article reduced or prevented from the occurrence of blisters in spite of a phenol resin contained therein by bringing a cross-linking composition comprising a specific component into contact with the phenol resin and heat-treating the resultant molded and cross- linked article at a high temperature. SOLUTION: (A) A cross-linking composition comprising (i) nitrile group- containing low-unsaturated copolymer organic polymer and (ii) an organic peroxide in an amount of 1-10 pts.wt. based on 100 pts.wt. component (i) is brought into contact with (B) a phenol resin and molded and cross-linked to provide (C) a nitrile group-containing organic polymeric article, which is then heat- treated at a high temperature of at least 120 deg.C. The component (i) is preferably a nitrile group-containing copolymer rubber having <=30 iodine value. Furthermore, the molding and cross-linking are preferably carried out at 160-200 deg.C for 2-10min heating time. The heat treatment is preferably performed at 140-170 deg.C for at least 10hr heating time. The article is especially effective in a shaft sealing for air conditioners of automobiles, etc.